2019
DOI: 10.3748/wjg.v25.i21.2683
|View full text |Cite
|
Sign up to set email alerts
|

Association of proton pump inhibitors with risk of hepatic encephalopathy in advanced liver disease: A meta-analysis

Abstract: BACKGROUND Several studies have explored the association between the use of proton pump inhibitors (PPIs) and the risk of developing hepatic encephalopathy (HE) in patients with advanced liver disease. However, the evidence-based conclusions are controversial. We hypothesized that using PPIs may increase the risk of HE in patients with advanced liver disease. If confirmed, clinicians must strictly adhere to the indications for PPI treatment in this population. AIM To ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 47 publications
2
18
0
1
Order By: Relevance
“…PPI use increases the risk of developing HE in patients with cirrhosis [104] as well as the severity of HE [105]. Two recent meta-analyses confirmed the association [106,107] and the proposed mechanism is that PPIs induce bacterial overgrowth in the intestine [108]. It is known that PPIs do not only change the bacterial composition in the stomach, but also in faeces with a significant shift towards oral flora in principal coordinate analyses (PCoA) [109,110], demonstrating that the entire gastrointestinal tract is affected downstream of gastric hypoacidity.…”
Section: Resultsmentioning
confidence: 99%
“…PPI use increases the risk of developing HE in patients with cirrhosis [104] as well as the severity of HE [105]. Two recent meta-analyses confirmed the association [106,107] and the proposed mechanism is that PPIs induce bacterial overgrowth in the intestine [108]. It is known that PPIs do not only change the bacterial composition in the stomach, but also in faeces with a significant shift towards oral flora in principal coordinate analyses (PCoA) [109,110], demonstrating that the entire gastrointestinal tract is affected downstream of gastric hypoacidity.…”
Section: Resultsmentioning
confidence: 99%
“…PPIs are independent risk factors for small intestinal injury or exacerbated NSAIDsinduced small intestinal injury 2 . After the review was published, systematic review and/or meta-analysis reported that there were adverse effect of hepatic encephalopathy in advanced liver disease 3 , gastric cancer 4 , and myocardial infarction/stroke 5 , etc. I believe that, at least in countries where rebamipide 2 can be used, PPIs should not be used to prevent upper gastrointestinal events due to NSAIDs.…”
mentioning
confidence: 99%
“…New articles on contemporary topics such as PPI safety are regularly added to the global medical literature, which may make it difficult to sum- With this letter, we would like to expand on the work of Salvo et al by mentioning six more recent meta-analyses that were published after their search date. [3][4][5][6][7][8] (Table 1) Several additional adverse effects of PPIs have been evaluated such as increased risk of hepatocellular carcinoma, pancreatic cancer, congenital malformations, and complications in patients with cirrhosis including spontaneous bacterial peritonitis, pneumonia and hepatic encephalopathy.…”
Section: Letter: Mind the Gap -Search And Publication Date Of Systematic Reviews And Meta-analysismentioning
confidence: 99%